2016
DOI: 10.1080/2162402x.2015.1128611
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis

Abstract: Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 31 publications
0
48
0
2
Order By: Relevance
“…Of the 1892 unique studies identified using our search criteria, 61 studies fulfilled our inclusion criteria and were included in the qualitative analysis (38 full text articles, 23 in abstract form) . Results of our search strategy are depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1892 unique studies identified using our search criteria, 61 studies fulfilled our inclusion criteria and were included in the qualitative analysis (38 full text articles, 23 in abstract form) . Results of our search strategy are depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two reports showed CMV reactivation in patients with refractory irColitis during immunosuppressive therapy. Lankes et al [6] reported a first case of irColitis that was resistant to corticosteroids and infliximab due to CMV reactivation. Franklin et al [7] reported that 5 of 41 patients with irColitis were refractory to immunosuppressive therapy, and all these therapy-refractory cases had detectable CMV.…”
Section: Discussionmentioning
confidence: 99%
“…However, these treatments may increase the susceptibility to infections. Recently, a few reports showed that cytomegalovirus (CMV) reactivation might be involved in the pathogenesis of refractory gastrointestinal irAEs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…During immunotherapy, the cellular components of intestinal bacteria interact with pattern recognition receptors to promote intestinal dendritic cell activation, boost differentiation and activation of Th17 cells; this is a high‐risk factor for severe gastrointestinal infections, such as Clostridium difficile infection (CDI) . Additionally, long‐term systematic corticosteroid treatment (>30 days) and immunosuppression may be associated with an increased risk of gut infection, or virus reactivation . Corticosteroids have an immunosuppressive effect mainly by disrupting T lymphocyte and monocyte functions and blocking the production of inflammatory cytokines; thus, there is a major risk of CDI with long‐term corticosteroid administration .…”
Section: Discussionmentioning
confidence: 99%